ANALYSIS OF TECHNOLOGY ADAPTATION IN LEARNING AT DEMANGAN 1 BANGKALAN ELEMENTARY SCHOOL - Dio Barrabas; Cahyani Setyatika Ramadhani; Robiatun Hasanah; Kinanto Kinanto (maktab: Jurnal Pendidikan dan Teknologi, 2022)
One of the tasks of the Asistensi Mengajar student participants is to assist students and teachers in terms of technology adaptation. The purpose of this research is to describe the application of learning in Demangan 1 Bangkalan Elementary School class using technology. This research is a qualitative descriptive study with the research subjects being students and teachers in class VB Demangan 1 Bangkalan Elementary School. Data collected using observation techniques, interviews, and documentation. The results of this study indicate that teachers and students use digital technology-based media in the form of power points and videos several times. Teachers have the ability to compile the media themselves, but at some times the teacher uses sources from Google or YouTube. In the learning process using these two media, students look active and focused so that learning is conducive. This technological adaptation also received a positive response from the school, namely by providing adequate facilities and infrastructure to carry out technological adaptation in the classroom. Based on the results of this study, it can be concluded that the technology adaptation in class V of Demangan 1 Bangkalan Elementary School  has been implemented properly.